2021
DOI: 10.3389/fmicb.2021.615893
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals a Novel Mechanism of Antiviral Immunity Upon Sacbrood Virus Infection in Honey Bee Larvae (Apis cerana)

Abstract: The honey bee is one of the most important pollinators in the agricultural system and is responsible for pollinating a third of all food we eat. Sacbrood virus (SBV) is a member of the virus family Iflaviridae and affects honey bee larvae and causes particularly devastating disease in the Asian honey bees, Apis cerana. Chinese Sacbrood virus (CSBV) is a geographic strain of SBV identified in China and has resulted in mass death of honey bees in China in recent years. However, the molecular mechanism underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…The colonization resistance conferred by the gut microbiota through stimulating the host’s innate immune system was supported by increasing evidence ( Lawley and Walker, 2013 ). The innate immune system of honeybees comprises the Toll and Imd pathways ( Lourenço et al, 2013 , 2018 ; Danihlík et al, 2015 ), which primarily regulate the production of antimicrobial peptides (AMPs), such as abaecin, apidaecin, defensin, and hymenoptaecin, during pathogen infection ( Evans et al, 2006 ; Guo et al, 2021 ). When honeybees were colonized with conventional gut microbiota or mono-colonized with strains from S. alvi , the immune system of honeybees was stimulated to inhibit potential pathogens such as Serratia marcescens ( Horak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The colonization resistance conferred by the gut microbiota through stimulating the host’s innate immune system was supported by increasing evidence ( Lawley and Walker, 2013 ). The innate immune system of honeybees comprises the Toll and Imd pathways ( Lourenço et al, 2013 , 2018 ; Danihlík et al, 2015 ), which primarily regulate the production of antimicrobial peptides (AMPs), such as abaecin, apidaecin, defensin, and hymenoptaecin, during pathogen infection ( Evans et al, 2006 ; Guo et al, 2021 ). When honeybees were colonized with conventional gut microbiota or mono-colonized with strains from S. alvi , the immune system of honeybees was stimulated to inhibit potential pathogens such as Serratia marcescens ( Horak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The indirect immune regulation of honeybees and other insects in response to gut commensals consists of three levels of resistance: physical barriers, cell-mediated immunity, and cell-free humoral immunity ( 20 ). Induction of honeybee innate immune responses by the gut microbes have been proposed, while only several bee gut members have been tested, such as Snodgrassella alvi ( 21 ), Lactobacillus kunkeei ( 23 ), and Frischella perrara ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Honeybee antibacterial immunity relies on the Toll and Imd pathways, which primarily regulate the production of AMPs released into circulation under the activation of the two signal pathways during pathogen infection ( 19 ). In honeybee, four families of AMPs—abaecin, apidaecin, defensin, and hymenoptaecin—have been recognized, which are key components of the innate immune system of honeybee ( 20 ). So far, several studies have shown that the gut microbiota can influence bee health by the modulation of host immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Зважаючи на те, що у Apis mellifera відсутній адаптивний імунітет [30], основні складники їх антиінфекційного захисту -вивільнення антимікробних пептидів, фагоцитоз, меланізація та ферментативне руйнування патогенів [31,32]. У відповідь на інфікування ВМР у бджіл також активується РНК-інтерференція [33,34]. Зважаючи на дані [35] щодо мінімальної віруліцидної дії нано-СеО2 проти вірусів, які не мають суперкапсиду, а ВМР належить до їх числа, антивірусна ефективність нано-СеО2 може бути пов'язана саме із впливом на неспецифічну ланку антиінфекційного захисту.…”
Section: тривалість (доби спостереження) виживання 50 % ізольованих у...unclassified